Redbay Ambrosia Beetle Xyleborus glabratus Eichhoff (Insecta: Coleoptera: Curculionidae: Scolytinae) - Rajinder Mann; Jiri Hulcr; Jorge E. Peña; Lukasz Stelinski (EDIS)
Ambrosia beetles are wood-degrading insects that live in nutritional symbiosis with ambrosia fungi. Usually we consider ambrosia beetles beneficial because they accelerate the decay of dead trees, which is important for nutrient cycling in healthy forests. However, the redbay ambrosia beetle and its fungal symbiont transmit the causal pathogen of laurel wilt disease among plants in the Laurel family (Lauraceae). They are considered a “very high risk” invasive disease pest complex having potential equal to that of Dutch elm disease or chestnut blight. Laurel wilt is a relatively new disease, and much is still unknown about how it will impact the flora of North America. This revised 7-page fact sheet highlights what we do know about this important new pest. Written by Rajinder Mann, Jiri Hulcr, Jorge Peña, and Lukasz Stelinski and published by the UF Department of Entomology and Nematology, May 2011.